2006
DOI: 10.1016/j.cell.2006.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Metastasis: Building a Framework

Abstract: Metastasis occurs when genetically unstable cancer cells adapt to a tissue microenvironment that is distant from the primary tumor. This process involves both the selection of traits that are advantageous to cancer cells and the concomitant recruitment of traits in the tumor stroma that accommodate invasion by metastatic cells. Recent conceptual and technological advances promote our understanding of the origins and nature of cancer metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
3,073
0
31

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 3,784 publications
(3,131 citation statements)
references
References 104 publications
27
3,073
0
31
Order By: Relevance
“…Circulating tumor cells (CTCs) are cells that flow into blood vessels or lymphatics from the primary tumor to circulate through the whole body. (27,28) CTCs are found at 1-10 cells per 1 mL of whole blood in patients with metastatic disease; 0.01% of CTCs detached from the primary tumor form metastases. (29,30) In the present study, no difference in prognosis based on GRWR was found among patients with HCC within the Milan criteria, whereas a significant increase in recurrence rates and a decrease in survival rates were observed in patients with HCC beyond the Milan criteria who received SFSG.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating tumor cells (CTCs) are cells that flow into blood vessels or lymphatics from the primary tumor to circulate through the whole body. (27,28) CTCs are found at 1-10 cells per 1 mL of whole blood in patients with metastatic disease; 0.01% of CTCs detached from the primary tumor form metastases. (29,30) In the present study, no difference in prognosis based on GRWR was found among patients with HCC within the Milan criteria, whereas a significant increase in recurrence rates and a decrease in survival rates were observed in patients with HCC beyond the Milan criteria who received SFSG.…”
Section: Discussionmentioning
confidence: 99%
“…However, the importance of tumorstromal interactions in cancer progression is increasingly recognized and it is possible that factors secreted by reactive cellular elements may help propagate tumor invasion. 40 The interpretation of p16 immunoreactivity in endometrial cancer is problematic as it is not always clear whether a 'positive' or 'negative' staining reaction represents the abnormal finding. In gynecological pathology generally, p16 immunostaining has been used most widely as an adjunct to diagnosis in cervical biopsy specimens.…”
Section: Endometrial Carcinoma Invasionmentioning
confidence: 99%
“…The development of metastases consists of a complex series of events accomplished by tumour cells after they acquire numerous abilities, one of which being the acquisition of an invasive potency. This mainly lies into an enhanced migration and the ability to digest the extracellular matrix (Gupta and Massague, 2006). Cell migration involves dynamic cytoskeletal changes and is highly regulated by the intracellular concentration of calcium.…”
Section: Introductionmentioning
confidence: 99%